Set-Based Concurrent Engineering Model for Automotive Electronic/Software Systems Development - Al-Ashaab, Ahmed; Howell, S.; Usowicz, K.; Hernando Anta, P.; Gorka, A. (Cranfield University Press, 2009)
This paper is presenting a proposal of a novel approach to automotive electronic/software systems development. It is based on the combination of Set-Based Concurrent Engineering, a Toyota approach to product development, with the standard V-Model of software development. Automotive industry currently faces the problem of growing complexity of electronic/software systems. This issue is especially visible at the level of integration of these systems which is difficult and error-prone. The presented conceptual proposal is to establish better processes that could handle the electronic/software systems design and development in a more integrated and consistent manner.
Organised by: Cranfield University
Keywords: Set-Based Concurrent Engineering; V-model; automotive electronic/software systems development